DISTINCTIVE COLLECTIVIST IDENTITY ON DIGITAL ADS: HARI RAYA AND LEBARAN 2021 - Marta, Rustono Farady; Supina, Supina; Rashid, Sabrina Mohd; Karolina, Cut Meutia; Naseer, Moazzam (Interaksi: Jurnal Ilmu Komunikasi, 2022)
Every family has a particular moment, especially in Malaysia and Indonesia, where the majority of the population is Muslim, where Eid al-Fitr has established a tradition for bringing family members closer together. Simply said, the tradition is known as "Hari Raya” whereas, in Indonesia, the term "Lebaran" is used. The year 2021 will be remembered for the social restraints put in place to prevent the spread of COVID-19. This study aims to capture this once-a-year event, which will then be interpreted using Oswald's Marketing Semiotics strategy to juxtapose the two digital advertising media on the Youtube Channel for cellular operator brands in each country in the Interpretivism Paradigm using a qualitative approach based on Hofstede's Cultural Dimension Theory. The Hari Raya 2021 Maxis advertisement symbolizes the State of Malaysia, while the 2021 Lebaran advertisement from the Indosat Ooredoo Provider represents the State of Indonesia, both of which are displayed in binary opposition. The study's findings reveal a consistent pattern in promoting the country's collectivist identity, with marketing distinctiveness arising from a variety of key components. The dominant color is green, which has a characteristic Malaysian Muslim nuance in its advertising storyline with the theme "Raya Si Sakan," which represents the Malaysian Cultural Dimension of Short-Term Orientation and Masculinity. In contrast to the majority of the color yellow, the title "Bulan yang Baik," reflects the warmth of friendship in terms of the identical dimensions of Indonesian culture, which tends towards long-term orientation and femininity in terms of the majority of the color yellow.